2016
DOI: 10.4028/www.scientific.net/kem.721.290
|View full text |Cite
|
Sign up to set email alerts
|

High-Energy Method of Transformation of Casting Metals and Alloys to the Composite Materials

Abstract: Work related to the development of metal composite materials using effect of super-deep penetration (SDP) of powder particles. Composite materials are obtained from usual casting billets. During SDP process powder particles work as needles and the fibers are formed in metal matrix under dynamic interaction between powder particles and matrix material. Researchers showed high non-uniformity of the chemical composition of the processed material. Material was doped with a high amount of alloying elements at SDP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…An aliphatic polyurethane plastic with a low viscosity was chosen as a model material. The density of the model material is 1.07 g/cm 3 , the tensile strength is 21.8 MPa, and the hardness is 72 HSD. Polyurethanes are the most valuable and widely produced polymers in the industry.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An aliphatic polyurethane plastic with a low viscosity was chosen as a model material. The density of the model material is 1.07 g/cm 3 , the tensile strength is 21.8 MPa, and the hardness is 72 HSD. Polyurethanes are the most valuable and widely produced polymers in the industry.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on steel and aluminum samples have shown a significant effect of high-speed flows of powder particles on the structure and properties of materials. [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These areas intertwine with other matrix regions, powder particles. As a result, forming a polycrystalline reinforcing framework and an anisotropic composite material [ 8 ]. This physical phenomenon occurs only in a closed system.…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of this treatment is an achievement of impulse of high pressure in the range of very short intervals. During SDP process powder particles work as needles and the fibers are formed in metal matrix under dynamic interaction between powder particles and matrix material [5]- [6]. Dynamic loading of surfaces by powder streams may ensure the intensification of subsequent nitriding and increase the wear resistance of the resulting layer.…”
Section: Introductionmentioning
confidence: 99%